Melatonin: A Versatile Protector against Oxidative DNA Damage - Annia Galano (Molecules, 2018)
Oxidative damage to DNA has important implications for human health and has been identified as a key factor in the onset and development of numerous diseases. Thus, it is evident that preventing DNA from oxidative damage is crucial for humans and for any living organism. Melatonin is an astonishingly versatile molecule in this context. It can offer both direct and indirect protection against a wide variety of damaging agents and through multiple pathways, which may (or may not) take place simultaneously. They include direct antioxidative protection, which is mediated by melatonin’s free radical scavenging activity, and also indirect ways of action. The latter include, at least: (i) inhibition of metal-induced DNA damage; (ii) protection against non-radical triggers of oxidative DNA damage; (iii) continuous protection after being metabolized; (iv) activation of antioxidative enzymes; (v) inhibition of pro-oxidative enzymes; and (vi) boosting of the DNA repair machinery. The rather unique capability of melatonin to exhibit multiple neutralizing actions against diverse threatening factors, together with its low toxicity and its ability to cross biological barriers, are all significant to its efficiency for preventing oxidative damage to DNA.